Enhancing metal solubility and phytoextraction in soil under Indian mustard (Journal of Oilseed Brassica, 2026)
In phyto-extraction slow removal rate of metals by plant is the main constraint in the way of making effective use of this green technique in managing contaminated site. Hence, an attempt has been made to study the effect of selected organic and inorganic amendments on enhancing efficacy of phytoextraction of Zn, Cd and Pb in contaminated soil using Indian mustard (Brassica juncea cv. Pusa Vijay) as a test crop. Results indicated that Cd availability in soil was increased from 38.7 to 96.7% under different amendments, whereas Pb availability enhanced from 53.8 to 94.0%. All the amendments enhanced the EDTA and DTPA-extractable Zn, Cd and Pb in soil. Cadmium removal by shoot of mustard was enhanced to the extent of 125, 62.5, 175, 175 and 212% under green manure, EDTA, S+S oxidizing bacteria, metal solubilizing bacteria and green manure + metal solubilizing bacteria treated soil, respectively over control. Root parameters (i.e. root length, diameter, surface area) also improved under different amendments. Application of green manure and metal solubilizing bacteria was the most efficient in enhancing the Zn, Cd and Pb removal by Indian mustard and phytoextraction from practical point of view.